Effects of poly(oxyethylene)-block structure in polyetheramines on the modified carbon nanotube/poly(lactic acid) composites. (November 2015) - He, Wei-Syuan; Shih, Yeng-Fong; Lin, Jiang-Jen; Dai, Shenghong A.
Abstract: The hybrids of multi-walled carbon nanotube and poly(lactic acid) (MWCNT/PLA) were prepared by a melt-blending method. In order to enhance the compatibility between the PLA and MWCNTs, the surface of the MWCNTs was covalently modified by Jeffamine® polyetheramines by functionalizing MWCNTs with carboxylic groups. Different molecular weights and hydrophilicity of the polyethermaines were grafted onto MWCNTs with the assistance of a dehydrating agent. The results showed that low-molecular-weight Jeffamine® polyetheramine modified MWCNTs can effectively improve the thermal properties of PLA composites. On the other hand, high-molecular-weight and poly(oxyethylene)-segmented polyetheramine could render the modified MWCNTs of well dispersion in PLA, and consequently affecting the improvements of mechanical properties and conductivity of composite materials. With the addition of 3.0 wt% MWCNTs, the increment of E ′ of the composite at 40 °C was 79%. For conductivity, the surface resistivity decreased from 1.27 × 10 12  Ω/sq for neat PLA to 8.30 × 10 −3  Ω/sq for the composites.